Raba tipično govorjenih diskurznih označevalcev na spletu - Dobrovoljc, Kaja (Slavistična revija, 2018)
This article compares the usage of three speech-specific discourse markers in the Gos corpus of spoken Slovenian and the Janes corpus of user-generated content. The results confirm that the online usage of these expressions is much less common than in speech, but nevertheless significant, in particular on platforms encouraging interactive or dialogue-like communication. In online discourse, markers' semantic-based functions prevail, such as those relating to the addressee, checking for agreement, or attenuating an assertion. They intertwine with discourse-structuring functions, such as creating emphasis or turn managing. All three markers also exhibit some new contexts of online usage, such as addressing an unknown or generic addressee, producing a specific stylistic effect, and entering into new types of fixed multi-word expressions.
Keywords: diskurzni označevalci; Gos; govorjeni jezik; Janes; korpusno jezikoslovje; slovenščina; spletne vsebine